Individualism and Nonattainment of Social Change in Chinua Achebe's Things Fall Apart and Arrow of God - Ohia, Ben-Fred (European Journal of Linguistics, 2023)
Purpose: In a society where many believe that only the mailed fist can maintain discipline, a refreshingly different point of view is reached by the comparison of two of Chinua Achebe's novels: Things Fall Apart and Arrow of God. The purpose of this paper is to explore the viewpoint presented in these novels by comparing their two heroes - Okonkwo and Ezeulu. They are compared first as revolutionary characters and second as revolutionary leaders, using as a guide Calvert's (1996) claims that individual leaders are not necessarily revolutionary leaders. Okonkwo and Ezeulu are seen to be both leaders and revolutionaries; they fail however, as revolutionary leaders for the simple but unarguable reason that they have no supporters. Methodology: Methodological procedures are adopted which include description of the study's sampling and method of data analysis. The study adopts a simple survey design. Findings: The paper in its findings discovers that individualism cannot thrive in a revolution of a society rather it is collective effort that appears to be more effective in a revolutionary struggle such as fou nd in Umuofia and Umuaro respectively. The paper concludes that followership marks an authentic revolutionary leader as the non-support of Okonkwo and Ezeulu in the novels leads to their tragic end. Unique contribution to theory, policy and practice: The paper recommends communalism as a way out of African socio-political barriers and posits that individuality cannot bring the social change and total liberation in African continent.